First Report of Pembrolizumab Activity in KIT-Mutated Thymic Carcinoma - Tommaso Martino De Pas; Giuseppe Giaccone; Chiara Catania; Fabio Conforti; Laura Pala; Periklis Mitsakis; Pierre-Yves Dietrich (Current Oncology)
The antitumor activity of immunotherapy is strongly influenced by the presence of driver gene mutations/translocations. For this reason, knowledge of the predictive value of specific genetic alterations in relation to anti-PD(L)1 activity is highly useful for the clinical decision making process in many solid tumors, particularly in Non-Small Cell Lung Cancer. Although data on the correlation between genetic alterations and response to immunotherapy are available in the majority of common cancers, data are lacking in the subset of patients with KIT-mutated Thymic Carcinoma (TC). As a consequence, although immunotherapy is a standard treatment for TC patients, the lack of this knowledge leads to uncertainty when proposing immunocheckpoint inhibitors in this subset of patients. Here we describe the first report of a patient with KIT-mutated TC who received the anti-PD1 agent pembrolizumab, which caused a sustained partial response. This case report of a sustained partial response achieved with pembrolizumab in a patient with KIT-mutated TC after progression to chemotherapy and imatinib may be supportive during clinical decision making for this extremely rare disease.